2022
DOI: 10.1002/lt.26417
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative risk factors of acute kidney injury after liver transplantation

Abstract: Acute kidney injury (AKI) is one of the most common complications of liver transplantation (LT). We examined the impact of intraoperative management on risk for AKI following LT. In this retrospective observational study, we linked data from the electronic health record with standardized transplant outcomes.Our primary outcome was stage 2 or 3 AKI as defined by Kidney Disease Improving Global Outcomes guidelines within the first 7 days of LT. We used logistic regression models to test the hypothesis that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…The length of ICU stay was significantly increased in the AKI group. Therefore, as reported in previous studies, we similarly demonstrate that post-LT AKI may lead to serious complications and cause worse prognosis ( 2 , 4 , 10 , 13 , 19 , 30 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The length of ICU stay was significantly increased in the AKI group. Therefore, as reported in previous studies, we similarly demonstrate that post-LT AKI may lead to serious complications and cause worse prognosis ( 2 , 4 , 10 , 13 , 19 , 30 ).…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have indicated that intraoperative events have a crucial role in the development of post-LT AKI; therefore, we intended to collect as many intraoperative variables as possible ( 3 , 13 , 14 ). The intraoperative data in this study included the operation time, anhepatic time, inferior vena cava occlusion time, intraoperative hypotension, estimated blood loss, fluid administration (crystalloid and colloid), intraoperative transfusion [red blood cell (RBC), fresh frozen plasma (FFP) and platelet], intraoperative drug dosage (furosemide and insulin), total urine volume and anhepatic phase urine volume.…”
Section: Methodsmentioning
confidence: 99%
“…We consider AKI more a biomarker for a renal insult than it is an outcome in and of itself as the majority of cases of AKI in liver transplant will resolve and in fact are treated by the liver transplant itself. 25 However, as a biomarker for injurious hypoperfusion it is generalizable and available at all transplant centers. Wang et al reported on their exceptionally high-risk patient population that a MAP of <60 mm Hg could be tolerated for up to 120 min without increasing the risk of 30-day mortality from the 7.6% reported.…”
Section: Discussionmentioning
confidence: 99%
“…We consider AKI more a biomarker for a renal insult than it is an outcome in and of itself as the majority of cases of AKI in liver transplant will resolve and in fact are treated by the liver transplant itself 25 . However, as a biomarker for injurious hypoperfusion it is generalizable and available at all transplant centers.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Pre-LT and perioperative AKI is also a risk factor for posttransplant chronic kidney disease. [1,2] Several perioperative factors have been linked to the development of AKI, such as intraoperative inotropic/vasopressor use, transfusion requirement, acid/base imbalance, and hypoalbuminemia. [2] The association of low serum albumin levels with a higher incidence of AKI has been suggested by multiple groups and is thought to be, at least partly, related to the protective antioxidant effects of albumin against ischemia-reperfusion injuries.…”
mentioning
confidence: 99%